poRsCHE: Remote Control via Head movEs - Lourenço, José Alberto Porfírio Pequeno (2018)
We present an ergonomic, nonintrusive and low power Embedded System which allows tetraplegic people to control an electric wheelchair by using their head movements. These command movements are implemented by taking into account people’s physical limitations. The main sensing device is installed in a low weight board attached to the user head via an elastic band. Wireless communication is implemented with Bluetooth 4.0 (Bluetooth Low Energy) which assures an ergonomic (non-existence of cables) and a low power battery operated system. A smartphone connection provides extra functionality which triggers an emergency contact call after identifying a user fainting condition.